حكم السرقة في الفقه الإسلامي: دراسة مقارنة - إسماعيل، منهل يحيى; أمين، سهام فاضل محمد (جامعة الموصل - كلية التربية الأساسية, 2019)
The theft crimes are regarded as one of the social phenomenon. They will be worst if the theif used violent with a victim to take his / her monyor belongings. The theif sometimes dare to kill the victim. In Islam, there is a rule to deal with such problem. Allah said in the Holy Quran " And eat up not one another's property un justly ( in any illegal way e.gstealing, robbing, deceiving nor give bribery to the rulers (judges before preseuting your cases) that you may knowingly eat up a part of the property of others sinfully (AL – Bagarah-188)and Allah also said (the male thief and the female thief, cut off ( from the wrist joint ) their ( right) hands as a recompense for that which they committed, a punishment by way of example from Allah. And Allah is All – powerfull, All – wise (AL – Ma,ldah–38).
الحمد لله وكفى، وسلام على رسله الذين اصطفى، وعلى خاتمتهم المجتبى، وعلى آلة وصحبه أئمة الهدى، ومن بهم اقتدى فاهتدى، وبعد: إن جريمة السرقة ظاهرة اجتماعية لم تكن وليدة عصر دون عصر وإنما هي ملازمة للإنسان حيث تأخذ اشكالا وصورا مختلفة تبعا لنوعية النظام الاجتماعي، إلا أن ظاهرة الإجرام مهما تغيرت واختلفت باختلاف المجتمعات فإن بعض الجرائم تبقى معروفة في المجتمعات ومعاصرة له، وفي كل وقت وزمان، ومن هذه الجرائم جريمة السرقة التي تكمن خطورتها إذا ما اقترنت بالعنف فإنها تتعدى فالسرقة تمس حياة الإنسان وسلامته خصوصا إذا ما داهم السارق الخطر الضحية لم تطاوعه بالتنازل عما بحوزته من مال.
Keywords: جرائم السرقة -- الأحكام الشرعية -- الفقه الإسلامي